PARADIGMA PENDIDIKAN ISLAM (Definisi, Arah, Dasar dan Ruang Lingkupnya) - Zainuddin, Mohammad Riza (EDUKASI: Jurnal Pendidikan Islam, 2013)
Islamic education is one of the leading human empowerment, good thoughts, mental and moral, to undertake humanitarian functions performed as a form of a servant of God and also as a custodian of this universe. The definition of Islamic education is to determine the maximum of effort from the base personality of the students, as elaborated in the al-Quran and al-Sunnah. To the effect of the Islamic Education is shaping the personality of Islam, Islamic tsaqÃ¢fah master, master of science and technology (Science and Technology) Principles of Islamic education is the integration, balance, equality, education for life.